Antioxidant response and oxidative damage induced by a swimming session: Influence of gender - Tauler, P.; Ferrer, M. D.; Romaguera, D.; Sureda, A.; Aguil, A.; Tur, J.; Pons, A. (Journal of Sports Sciences, 2008)
In this study, we examined oxidative stress after a swimming session, the responses of the antioxidant defences, and the influence of gender on these responses. Fifteen boys and eight girls participated voluntarily in the study. Plasma concentrations of 17-ß-estradiol, vitamin E, retinol, carotenes, ascorbate, malondialdehyde, and the carbonyl index were determined. Creatine kinase, gamma glutamyl transpeptidase, and lactate dehydrogenase activities, as well as glucose, urea, urate, cholesterol, and triglycerides, were determined in serum. Plasma concentrations of 17-ß-estradiol were higher in girls than in boys. Exercise increased plasma ascorbate both in boys and in girls. Malondialdehyde increased in boys but was maintained in girls after exercise. Creatine kinase values corrected for lean body mass were similar in boys and girls at baseline, but the post-exercise values in boys were higher than in girls. A positive correlation was observed in boys, but not in girls, between plasma malondialdehyde and creatine kinase corrected concentrations. Furthermore, a negative correlation was observed between the increase in circulating neutrophils and in creatine kinase activity in girls but not in boys. In conclusion, a swimming session induced higher muscular and oxidative damage in boys than in girls.